Comparative analysis of the experience of European countries in the legal provision of information security of children - Akimzhanova, М.T.; Tilep, T.S. (Bulletin of the Karaganda University “Law Series”, 2024)
Among those requiring priority protection of children's rights is their right to information security, which implies ensuring the protection of society and the state from those types of information that pose a danger to the life and health of children or may harm their normal moral, spiritual, mental and physical development. Legal provision of information security for children is a complex and dynamic task that requires not only appropriate legislative support, but also broad involvement of society, technological readiness, as well as constant analysis and adaptation to new challenges and opportunities. The article provides a comparative analysis of legislative acts, strategies and practices using the example of the legislation of the United States of America, Great Britain, Germany, France, and Germany. The authors highlight common trends and differences in approaches to regulating children's information security, as well as identify successful practices and challenges faced by individual European countries. Important attention is paid to the effectiveness of legal instruments and measures aimed at reducing threats in the online environment and creating a safe space for children's development. The methodological basis of the research consists of general scientific methods of cognition of social phenomena and processes, methods of scientific analysis and synthesis. The results of the study were the possible measures proposed by the authors to improve the system of legal provision of information security for children in the Republic of Kazakhstan.